Co-crystal Structure of Thermosynechococcus elongatus Sucrose Phosphate Synthase With UDP and Sucrose-6-Phosphate Provides Insight Into Its Mechanism of Action Involving an Oxocarbenium Ion and the Glycosidic Bond - Li, Yuying; Yao, Yuan; Yang, Guosong; Tang, Jun; Ayala, Gabriela Jaramillo; Li, Xumin; Zhang, Wenlu; Han, Qiuyu; Yang, Tong; Wang, Hao; Mayo, Kevin H.; Su, Jiyong (Frontiers in Microbiology, 2020)
In green species, sucrose can help antagonize abiotic stress. Sucrose phosphate synthase (SPS) is a well-known rate-limiting enzyme in the synthesis of sucrose. To date, however, there is no known crystal structure of SPS from plant or cyanobacteria. In this study, we report the first co-crystal structure of SPS from Thermosynechococcus elongatus with UDP and sucrose-6-phosphate (S6P). Within the catalytic site, the side chains of His158 and Glu331, along with two phosphate groups from UDP, form hydrogen bonds with the four hydroxyl groups of the glucose moiety in S6P. This association causes these four hydroxyl groups to become partially negatively charged, thus promoting formation of the C1 oxocarbenium ion. Breakage of the hydrogen bond between His158 and one of the hydroxyl groups may trigger covalent bond formation between the C1 oxocarbenium ion and the C2 hydroxyl of fructose-6-phosphate. Consistent with our structural model, we observed that two SPS mutants, H158A and E331A, lost all catalytic activity. Moreover, electron density of residues from two loops (loop1 and loop2) in the SPS A-domain was not observed, suggest their dynamic nature. B-factor analysis and molecular dynamics stimulations of the full-length enzyme and A-domain indicate that both loops are crucial for binding and release of substrate and product. In addition, temperature gradient analysis shows that SPS exhibits its highest activity at 70°C, suggesting that this enzyme has the potential of being used in industrial production of S6P.